(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Research will focus on investments for the development of the company. Transition to the circular economy is understood in many cases only as an unnecessary obstacle, not as the new business model. Production based on the linear model "take, make, dispose of" is not possible anymore based on decreased environmental quality. Increased production efficiency could help promote the company's prestige, gain tax allowances, create optimistic co-operation with the state, municipality, and maintain sustainability in terms of the balance achieved between economic, environmental and social interests. Although the research until now is in an early stage, the research purpose is to create an adapted model for the implementation of the circular economy for the small and medium enterprises (from now on – SMEs) of Latvia in a long-term perspective. Research will focus on the following qualitative data analysis methods – SWOT, factor, economic contribution, structured interviews at expert level, overall structured interview in the form of the questionnaire. From quantitative methods, hierarchical cluster or partial cluster method will be used in this research, analysing 3966 organisations in the Eco-Management and audit scheme (from now on – EMAS) at the European level that ensure compliance with the essential environmental requirements under EMAS Regulation No.1221/2009 . Until now within the research, the number of EMAS organisations have been selected between 29 different countries (total number of observations) in 5 sectors (energy, water, waste management, food industry, port terminals), allowing to make the cross-country comparison and describe the involvement level of EMAS in each country. Before using the cluster method, it is essential to assess the cluster trend and whether the cluster method is suitable for research data. The next step will involve using a hierarchical cluster or partial cluster method (a certain number of clusters will be created). It is necessary to use different techniques to evaluate and interpret the created cluster results in future work. Until now, the main conclusion from the literature study is that Latvia has no organisation registered under EMAS and the term "circular economy" is a prevalent trend nowadays worldwide, which can be justified with 114 different terms of the circular economy. Expected results will be the following – issued new criteria for SMEs, issued the adapted model and issued recommendations and suggestions for developing the eco-innovation market.